Monitoring device for electronics components inventory management system of FKP - Zahairin, Zakaria (2013)
This project aim to facilitate inventory management system in term of reservation, borrowing and returning electronics component in electronics laboratory. Generally, the focus of this project to overcome the problem in detecting the quantity of component in laboratory.This project usually monitoring and managing the inventory system in laboratory. This final year project carry out by the author to fulfillment the requirement for award the degree of Bachelor Mechatronics Engineering. This project give the student easy to take the electronics component and the duty staff can manage electronics laboratory in systematics way and flexible on time. This project only need the student to keep in the data of component in online form then print it. After that, scan the code with barcode scanner and receive the component when indicator show pass and unlock the system. The result will show when output 1 (drawer 1), output 3 (drawer 2) and output 5 (drawer 3) were on and the plunger will unlock.The remaining time will delay 25 second to lock back the system. The inventory management system is important to all staff and student especially in Faculty of Manufacturing department as the guided and easier way to keep in track of record.